Mały teatrzyk wielkiego przełomu wieków - Anna Szwed (Postscriptum Polonistyczne)
The article presents an account of how the Polish language course taught by Polish lecturers at Sofia University at the end of the twentieth–and the beginning of the twentyfirst century resulted in the establishment of the educational theatre as an unconventional, creative and extremely successful form of improving the students’ knowledge and practice of Polish language by staging literary works in a creative way with literary studies, theatrical skills and language studies coming together in this venture. In 2000 the theater staged the play A Window Open to the Wind based on poems by the Polish Sappholike poetess Maria PawlikowskaJasnorzewska. The play was performed to celebrate the opening of the Polish studies room at the University. The next performance staged the play Eutedemis. A Manuscript Found on the Internet based on a poem by the young poetess Małgorzatа Kapicа. These performances fulfill multiple aims and first and foremost they do help develop practical language skills.